Penyalahgunaan Karya Cipta Buku Novel Melalui Media Internet - Holdrin Nahumury; Nancy Silvana Haliwela; Judy Marria Saimima (Faculty of Law Universitas Pattimura, 2023)
The Copyright Law and the Civil Code regulate the provision of protection for the rights of a person to protect a work of creation from the actions of other people who violate a person's copyright and cause harm to the creator/owner of a work of creation, but in reality until now there are still many violations of the copyright of novel books that are published through internet media which cause harm to the creator. Purposes of the Research For reviewing and misusing copyrighted works of books through internet media can be criminalized. and To study and explain how the form of compensation for misuse of copyrighted works of books in the civil aspect. and As one of the requirements in completing undergraduate studies (S1) at the Faculty of Law, Pattimura University, Ambon. The research method used is Normative Juridical, Type of research is Descriptive Analytical, Sources of legal materials: Primary, Secondary and Tertiary, Techniques for collecting legal materials using Literature Study, Analysis of legal materials using Qualitative method. The results of this study are Misuse of copyrighted works through internet media can be criminalized based on legal provisions Article 35 of Law Number 11 of 2008 concerning Information Technology and Communication (UU ITE) and Article 113 paragraph 1, paragraph 2, paragraph 3 and paragraph 4 of Law Number 28 of 2014 concerning Copyright (UUHC). And The form of compensation for the misuse of copyrighted works based on IPR and the Civil Code is by making compensation in the form of an amount of money paid to the owner of the copyrighted work and can be done through a request to the Commercial Court or the District Court related to Copyright infringement or Unlawful Acts as a result of misuse of copyrighted works through the internet media.